Gestión del talento humano y su influencia en la mejora del desempeño laboral de los colaboradores del Consorcio PRODES La Libertad, 2014. - Castro Rojas, Rosa Inés (2014)
The present study was conducted in La Libertad PRODES consortium of Trujillo, which has been determined that the lack of talent management causes, causing low job performance, which, no sense of experiential progress develops. The aim of this work is to determine how the talent management, improving work performance of employees PRODES LL Freedom Consortium. For its development it had primary information that is offered by the company and as secondary information was obtained from books, magazines, internet, etc. The methodology applied in the implementation of this research is qualitative agreement with the paradigm that was determined to be purposive that is critical to be discussed directly with every aspect related to the management of human talent. Finally it is necessary to found a training plan according to the real needs of management and operation of human talent required to improve job performance. The font used is the survey to workers of the consortium.